A geobotanical survey on acidophilous grasslands in the Abruzzo, Lazio and Molise National Park (Central Italy) - Di Pietro, Romeo; De Santis, Alessandro; Fortini, Paola (Lazaroa, 2006)
The acidophilous grasslands of the south-eastern part of the Abruzzo, Lazio and Molise National Park was studied by the phytosociological method and analyzed from a synecological viewpoint with the help of soil analysis. Four clusters of relevés resulted from the numerical classification. Syntaxonomically they were ascribed to the following associations: Poo violaceae-Nardetum strictae, Potentillo rigoanae-Festucetum paniculatae, Nardo strictae-Brachypodietum genuensis and Potentillo rigoanae-Brachypodietum genuensis. Since the original proposal of all the syntaxa identified in the present study were affected by nomenclatural mistakes, they were corrected in accordance with the rules of ICPN. The occurrence of Anthoxanto-Brachypodietum in central Apennines, is excluded since this association falls in syntaxonomical synonymy with Potentillo-Brachypodietum. The synecological analysis proved that the distribution of the different communities identified within the study area to be correlated with topographic, geomorphological and soil factors. Among these latter, the ratio H+/basic cations, pH behave as the most influencing parameters in the distribution of the communities identified.